ANALISIS PERSEPSI WISATAWAN TERHADAP KOTA MEDAN SEBAGAI KOTA YANG BERSAHABAT - Pedia Aldy (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2010)
The purpose of this research was to identify and analyze tourist's perception whom visited Medan as friendly city. tourist's perception was focused on safety factors of Medan city. tourist who never visitied and tourist who has visited Medan was mainly analyze. 112 international tourist was held as respondent.